2023
DOI: 10.1002/aenm.202203898
|View full text |Cite
|
Sign up to set email alerts
|

Ink Design Enabling Slot‐Die Coated Perovskite Solar Cells with >22% Power Conversion Efficiency, Micro‐Modules, and 1 Year of Outdoor Performance Evaluation

Abstract: The next technological step in the exploration of metal‐halide perovskite solar cells is the demonstration of larger‐area device prototypes under outdoor operating conditions. The authors here demonstrate that when slot‐die coating the halide perovskite layers on large areas, ribbing effects may occur but can be prevented by adjusting the precursor ink's rheological properties. For formamidinium lead triiodide (FAPbI3) precursor inks based on 2‐methoxyethanol, the ink viscosity is adjusted by adding acetonitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 54 publications
(76 reference statements)
0
38
0
Order By: Relevance
“…[ 24 ] By contrast, in the case of LSPI with relatively low surface tension and viscosity, the ink can transfer well from the meniscus guides to the hole transport layer and form a sufficiently wet film, resulting in a thick, uniform perovskite film. [ 15,20 ] Moreover, as described above, since the wet thin film of the perovskite precursor containing large colloids is quickly crystallized by external thermal energy, [ 20 ] a thick and uniform thin film can be formed (Figure S4, Supporting Information). The UV–vis light absorption spectrum indirectly shows that the thickness of the perovskite thin film increases with the increase of DCB addition, [ 25 ] which is consistent with the measured data using contact surface profiler (Alpha Step) (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] By contrast, in the case of LSPI with relatively low surface tension and viscosity, the ink can transfer well from the meniscus guides to the hole transport layer and form a sufficiently wet film, resulting in a thick, uniform perovskite film. [ 15,20 ] Moreover, as described above, since the wet thin film of the perovskite precursor containing large colloids is quickly crystallized by external thermal energy, [ 20 ] a thick and uniform thin film can be formed (Figure S4, Supporting Information). The UV–vis light absorption spectrum indirectly shows that the thickness of the perovskite thin film increases with the increase of DCB addition, [ 25 ] which is consistent with the measured data using contact surface profiler (Alpha Step) (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] In addition, the viscosity of the perovskite ink was controlled by adding acetonitrile (ACN) to the 2‐methoxyethanol‐based formamidinium lead triiodide (FAPbI 3 ) precursor ink, consequently, a slot‐die‐based smooth perovskite film with no ribbing effects and a minimodules (12.7 cm 2 ) with a PCE of 17.1% was achieved. [ 15 ] Further, the volatile cosolvent mixed to dilute the perovskite precursor ink to a low concentration (<0.5 m ) allowed it to maintain film quality and optoelectronic properties similar to those of the high concentration precursor (>1.4 m ), resulting in a high module efficiency of over 18%. [ 2a ] Thus, the rheological properties of the perovskite precursor ink are critical to the formation of perovskite thin films that crystallize from wet films through a process of nucleation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a shows a graphical representation of combinatorial SDC from dual feed inks where the ink1 is and ink2 is MAPbBr 3 dissolved in N,N-dimethylformamide (DMF). [19] Ink1 and ink2 are pre-mixed in a T connector and thus become ink 3, which is then fed into a die head. An image shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the strong interaction between PbI 2 and NMP, the NMP can accelerate the nucleation rate and decrease the formation energy. It is also found that acetonitrile (ACN) and 2-mercaptoethanol (2-ME) can quickly dry the FACs ink [50] and smooth the FA-based perovskite film [29]. However, the 2-ME has a low solubility of Cs + [23], which will inhibit its application in FACs perovskite.…”
Section: Solventsmentioning
confidence: 99%